Macrobiotus siamensis sp. n. (Eutardigrada, Macrobiotidae) from Thailand (Asia) - Tumanov, Denis V. (Zootaxa, 2006)
An illustrated description of Macrobiotus siamensis sp. n. from Thailand is given. The new species belongs to the furciger group and differs from the most similar species, Macrobiotus sicheli Binda, Pilato and Lisi, 2005, mostly by the absence of eyes, smooth cuticle and longer egg processes.